2011
DOI: 10.1097/scs.0b013e31821cc528
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Reactive Lymphoid Hyperplasia in a Child With Persistent Obstructive Sleep Apnea Despite Previous Tonsillectomy and Adenoidectomy

Abstract: Both lingual tonsil and adenoid are the lymphoid tissue members of Waldeyer ring. Enlargement of the lingual tonsil and adenoid occurs in children with persistent obstructive sleep apnea despite previous tonsillectomy and adenoidectomy relatively frequently.In this article, we present a case with upper airway obstruction and infection findings because of excessive lingual tonsil and adenoid tissue hyperplasia and, additionally, bilateral multiple cervical lymphadenopathies. The patient had had tonsillectomy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
0
10
1
Order By: Relevance
“…There appears to be a complex interplay with laryngopharyngeal reflux (LPR) emerging as a strong potential contributor to LTH and, subsequently, OSA. Previous authors have also demonstrated an association between LTH and OSA, BMI, age and smoking, but there has not been general agreement [1, 7]. This study adds further support to an association between a positive reflux finding score and BMI with lingual tonsil hypertrophy, but does not support a history of childhood tonsillectomy or age being associated with lingual tonsil size in adults.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…There appears to be a complex interplay with laryngopharyngeal reflux (LPR) emerging as a strong potential contributor to LTH and, subsequently, OSA. Previous authors have also demonstrated an association between LTH and OSA, BMI, age and smoking, but there has not been general agreement [1, 7]. This study adds further support to an association between a positive reflux finding score and BMI with lingual tonsil hypertrophy, but does not support a history of childhood tonsillectomy or age being associated with lingual tonsil size in adults.…”
Section: Discussioncontrasting
confidence: 69%
“…Sung et al demonstrated a correlation between BMI, reflux finding score and lingual tonsil hypertrophy in OSA patients [1]. A trend was also seen for a negative correlation with age, but was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations